Aflatoxin in cereals and groundnut from small holder farming households in Malawi. Issue 4 (2nd October 2022) - Gichohi-Wainaina, Wanjiku N.; Kumwenda, Nelson C.; Harry, Msere; Matumba, Limbikani; Njoroge, Samuel M. C.; Okori, Patrick
ABSTRACT: Aflatoxin contamination in commonly consumed cereals and nuts may place children at higher risk of stunting and adults at risk of developing liver cancer. This study investigated knowledge on aflatoxins and the level of aflatoxin B1 contamination in commonly consumed cereals and nuts in Malawi. It also included an examination of the proportion of cereals and nuts contaminated above regulatory maximum limits. Aflatoxin contamination in samples was assessed using an enzyme-linked immunosorbent assay (ELISA) method. Less than half of all households knew that consumption of aflatoxin contaminated grain is associated with stunting and lowered immunity. Sorghum samples were the most contaminated and millet the least contaminated. Aflatoxin contamination was highest in southern Malawi and least in northern Malawi. Observed results indicate that this population is at risk of poor health due to lack of knowledge and aflatoxin exposure. Strategies to address contamination should therefore include a comprehensive education campaign to increase knowledge and promote accessible strategies.